2017
DOI: 10.1002/jbmr.3116
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality After Pelvic Fractures Among Older People

Abstract: The study aimed to estimate excess mortality in patients aged 60 years or older up to 1 year after pelvic fracture compared with a population without pelvic fracture. In this retrospective population-based observational study, we use routine data from a large health insurance in Germany. For each patient with a first pelvic fracture between 2008 and 2010 (n ¼ 5685 cases, 82% female, mean age 80 AE 9 years), about 34 individuals without pelvic fracture (n ¼ 193,159 controls) were frequency matched by sex, age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 37 publications
6
40
0
3
Order By: Relevance
“…The reported average duration of hospital stay ranges from 9.3 to 45 days (3,14). The 1-year mortality ranges from 9.5% to 27% (3,13,33); these figures are similar to those reported for proximal femur fractures. Hill et al even reported a 5-year mortality of 54.4% (34).…”
Section: Complications and Prognosissupporting
confidence: 70%
“…The reported average duration of hospital stay ranges from 9.3 to 45 days (3,14). The 1-year mortality ranges from 9.5% to 27% (3,13,33); these figures are similar to those reported for proximal femur fractures. Hill et al even reported a 5-year mortality of 54.4% (34).…”
Section: Complications and Prognosissupporting
confidence: 70%
“…In consideration of these data [ 6 , 29 , 30 ] and the excess of mortality following a pelvic ring fracture in the elderly [ 31 ], surgical treatment might be favored especially for patients suffering from persistent pain and immobilization following a conservative treatment [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pelvis fractures constitute a significant clinical problem [6] [80] as they cause intense pain and immobility, impair the quality of life, and lead to loss of patients' independence [81]. In the elderly population, pelvis fractures are associated with a high morbidity and mortality with up to 27% of patients dying within 1 year of surgery [82,83].…”
Section: Pelvis Fracturesmentioning
confidence: 99%